The metabolic characteristics and changes of chondrocytes in vivo and in vitro in osteoarthritis - Adam, Miradj Siddick; Zhuang, Huangming; Ren, Xunshan; Zhang, Yuelong; Zhou, Panghu (Frontiers in Endocrinology, 2024)
Osteoarthritis (OA) is an intricate pathological condition that primarily affects the entire synovial joint, especially the hip, hand, and knee joints. This results in inflammation in the synovium and osteochondral injuries, ultimately causing functional limitations and joint dysfunction. The key mechanism responsible for maintaining articular cartilage function is chondrocyte metabolism, which involves energy generation through glycolysis, oxidative phosphorylation, and other metabolic pathways. Some studies have shown that chondrocytes in OA exhibit increased glycolytic activity, leading to elevated lactate production and decreased cartilage matrix synthesis. In OA cartilage, chondrocytes display alterations in mitochondrial activity, such as decreased ATP generation and increased oxidative stress, which can contribute to cartilage deterioration. Chondrocyte metabolism also involves anabolic processes for extracellular matrix substrate production and energy generation.During OA, chondrocytes undergo considerable metabolic changes in different aspects, leading to articular cartilage homeostasis deterioration. Numerous studies have been carried out to provide tangible therapies for OA by using various models in vivo and in vitro targeting chondrocyte metabolism, although there are still certain limitations. With growing evidence indicating the essential role of chondrocyte metabolism in disease etiology, this literature review explores the metabolic characteristics and changes of chondrocytes in the presence of OA, both in vivo and in vitro. To provide insight into the complex metabolic reprogramming crucial in chondrocytes during OA progression, we investigate the dynamic interaction between metabolic pathways, such as glycolysis, lipid metabolism, and mitochondrial function. In addition, this review highlights prospective future research directions for novel approaches to diagnosis and treatment. Adopting a multifaceted strategy, our review aims to offer a comprehensive understanding of the metabolic intricacies within chondrocytes in OA, with the ultimate goal of identifying therapeutic targets capable of modulating chondrocyte metabolism for the treatment of OA.